The mosque in Albanian folk literature - Muhamed Çitaku, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The mosque had a significant role in all the Muslim community. This religious institution has played a key role in the Albanians since the 14th century when the people accepted Islam and up to the present day. The significant role of the mosque has been reflected through several folkloric works, which serve as a memory for the deeds, worries, and problems of the Albanian people throughout their history. The main goal of this paper is then to put to the fore the image of the mosque on the Albanian folklore at different stages and times. The mosque in Kosovo has been examined from different historical, religious, and geographical perspectives, including the architecture and ornaments – the image by which the mosque is presented on the Albanian folklore, fulfils the current landscape with new data and promotes a deeper understanding of the mosque on its own. In this paper, we understand the role of the mosque in establishing the Islamic identity of Albanians, organization of Albanian society, education, culture, the Albanian state building, protection from national assimilation, and its great resistance during invasion. The results shown have been obtained using a statistical and hermeneutic approach.